Wavelength-Orthogonal Stiffening of Hydrogel Networks with Visible Light - Truong, Vinh X.; Bachmann, Julian; Unterreiner, Andreas-Neil; Blinco, James P.; Barner-Kowollik, Christopher (Angewandte Chemie International Edition, 2022)
Herein, we introduce the wavelength-orthogonal crosslinking of hydrogel networks using two red-shifted chromophores, i.e. acrylpyerene (AP, λactivation=410–490 nm) and styrylpyrido[2,3-b]pyrazine (SPP, λactivation=400–550 nm), able to undergo [2+2] photocycloaddition in the visible-light regime. The photoreactivity of the SPP moiety is pH-dependent, whereby an acidic environment inhibits the cycloaddition. By employing a spiropyran-based photoacid generator with suitable absorption wavelength, we are able to restrict the activation wavelength of the SPP moiety to the green light region (λactivation=520–550 nm), enabling wavelength-orthogonal activation of the AP group. Our wavelength-orthogonal photochemical system was successfully applied in the design of hydrogels whose stiffness can be tuned independently by either green or blue light.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hydrogels; Photoacid Generator; Photocycloaddition; Visible Light; Wavelength-Orthogonal